Korelasi Antara Sifat Sensori dan Fisikokimia Teh Hijau - Dede Robiatul Adawiyah; Miss Sathita Wisetsombat; Piyaporn Chueamchaitrakun (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2017)
. This research aimed to study the physicochemical properties especially phenolic content and color, sensory properties), and correlation between those parameters with sensorial properties of green teas from in different countries (Thailand, China, Indonesia, and Japan). The phenolic content was analyzed by the spectrophotometer. Color was analyzed by Chromameter using a white tile (D6:Y=94.4, x=0.3172, y=0.3339). The sensory properties for some sensory attributes of green tea (bitter taste, burn odor, fermented odor, astringency, and green odor) was performed by using quantitative descriptive analysis (QDA) method. The greatest amounts of total phenolic content (952.46 mg GAE/100 mL) were found for green tea leaves from Thailand (Am Nouy). The lowest amounts of total phenolic content were found from another tea samples with values ranging from 122.83 mg GAE/100 mL. The lowest color values of a* coming from Wawee Nature Group (-8.52) whereas the highest color value of a* was from Chanya (6.41). For Quantitative descriptive analysis, the burned fermented and aroma dry is teh Hijau Asli GMQ 2, Tong Tji, Chanya, Kepaladjenggot. Green and bitter is Teh Hijau Asli GMQ 1, Am nuoy, Royal project (TH), Wawee tea (TH), and Sencha. The positively correlation was found between bitter taste with green aroma, and b*; fermented with burned and aroma dry; dry aroma with burned and b*. The negatively correlation was found between burned aroma with total phenolic content and L*.